Deception, Desire, and Society in Restoration Comedy "The Country Wife" - Gol Man Gurung, (Interdisciplinary Journal of Management and Social Sciences, 2025)
The Restoration libertines were the successors of the Lucretian philosophical tradition, which emphasized the pursuit of physical and sensory pleasure in life. The primary objective of the libertines was to attain sexual pleasure by emancipating sexuality from societal constraints and the institution of marriage. In The Country Wife, a Restoration comedy by William Wycherley, the play's lewd humor and fast-paced plot center around a rake named Horner who feigns impotence to seduce women in the city. The story unfolds with elements of deception, jealousy, and societal critique, reflecting the Restoration period's focus on leisure and the arts. Through witty dialogue and sexual innuendos, the play explores the complexities of relationships and societal norms, challenging Puritan ideals and emphasizing the pursuit of pleasure and entertainment. The narrative unfolds with Horner orchestrating various schemes to pursue romantic interests while navigating the intrigues of high society. The juxtaposition of city life with country innocence adds depth to the characters' motivations and actions, creating a comical yet insightful commentary on human nature and desire during the Restoration era. Overall, The Country Wife remains a classic example of Restoration comedy, blending satire, humor, and social commentary to entertain and provoke thought among audiences.